THE EFFECT OF OPERATING CYCLE AND DEFAULT RISK ON PROFIT QUALITY WITH GOOD CORPORATE GOVERNANCE AS A MODERATION VARIABLE - Yayah Syahriyah; Iin Rosini; Nofryanti (ZILLZELL MEDIA PRIMA, 2024)
This study aims to examine the influence of operating cycle and default risk on profit quality with good corporate governance as a moderator. The research method used is an associative quantitative method. The data used in this study is panel data, which is a combination of time series data and cross section data. The population in this study is companies in the consumer goods industry sector listed on the Indonesia Stock Exchange in 2019-2023. The determination of samples by purposive sampling technique was obtained from 16 companies with 80 observation data. The analysis technique and hypothesis testing were carried out by panel data regression analysis through EViews ver-12. Based on the results of the T test, it is known that the operating cycle has a significant effect on the quality of profits. On the other hand, default risk has no effect on the quality of profits. Meanwhile, good corporate governance cannot moderate the influence of operating cycle variables and default risk variables on profit quality.